Extracorporeal shock wave therapy for equine musculoskeletal disorders: from biological mechanisms to clinical applications - Qiu, Zhongsheng; Wang, Jiaqi; Zhang, Yukun; Liu, Xiaxin; Wei, Chengwei; Ma, Tianwen (Frontiers in Veterinary Science, 2025)
Musculoskeletal injuries represent a primary cause of suboptimal performance and early retirement in equine athletes. To address this challenge, the veterinary community has long endeavored to develop safer and more effective therapeutic strategies. Extracorporeal shock wave therapy (ESWT), as a treatment for equine musculoskeletal injuries, has garnered substantial attention among equine veterinarians. Focused on the theme ESWT Therapy for Equine Musculoskeletal Disorders: From biological mechanisms to clinical applications, this article systematically reviews existing literature on the biological effects of ESWT—including analgesia, anti-inflammation, and autologous repair—mediated through diverse signaling pathways and factors. It synthesizes the current status of clinical applications and underlying mechanisms of ESWT in managing equine musculoskeletal conditions such as suspensory desmitis, superficial digital flexor tendinitis, osteoarthritis, navicular syndrome, and back pain syndrome. Additionally, the article summarizes relevant parameters for ESWT in treating different injuries, offering a reference for clinical equine veterinarians.